Analisis Hubungan Kepuasan Kerja Terhadap Loyalitas Karyawan Dalam Novel Gadis Minimarket Karya Sayaka Murata - Bagas Prasetyo Jati; Raden Rahardian Dwi Yogi Widayat; Eva Dwi Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
Human resources are an important aspect of a company. A company will not stand alone without a company, therefore, it is very important for companies to consider employee satisfaction and commitment. Employees with a high level of loyalty will bring many benefits to the company. In the novel Gadis Minimarket, a girl is named Keiko. Keiko is described as a hardworking woman. He has worked as a clerk at a minimarket for 18 years. She really liked the job because working as an employee made Keiko feel more appreciated and able to be herself. This is what makes Keiko have high loyalty to the company. From this novel, the researcher aims to analyze the relationship between job satisfaction and employee loyalty using qualitative descriptive methods. The results of the analysis carried out by researchers found that there is a positive relationship between job satisfaction and employee loyalty to the company.